MORPHOLOGICAL CHARACTERISTICS AND EXPERT ASSESSMENT OF CRANIOCEREBRAL INJURY - Tohir Kh. Zikrillaev; Ibragim I. Bakhriev (Central Asian Journal of Medicine, 2023)
The article is dedicated to morphological changes occurring in craniocerebral injury. Specifically, they often manifest as epidural, subdural, and subarachnoid hemorrhages. The sources of bleeding, their types, the mechanism of formation, and the morphological characteristics in craniocerebral injury are determined.